Humidity micro-climate characterisation in indoor environments: A benchmark study. (March 2020) - Bonello, M.; Micallef, D.; Borg, S.P.
Abstract: Humidity is an important parameter in understanding the micro-climate in indoor spaces. Existing literature focuses mostly on spatially averaged humidity levels leaving a gap on the spatio-temporal character of this variable. This is contrary to the well populated literature on other environmental parameters such as air temperature and air velocity. The aim of this paper is therefore twofold. First it presents transient humidity and temperature distribution experimental results for a test chamber containing a seated test subject. Secondly, using a validated Computational Fluid Dynamics model, humidity isotropy or lack thereof under conditions of a humidified jet of air was studied. The experimental measurements were carried out at specific points in space over a period of circa 2 h. The CFD model enabled a more complete understanding of the spatial and temporal variations occurring within the space. Comparing the experimental results with those from the CFD model shows that the latter manages to adequately predict the transient specific humidity distribution inside the chamber with a maximum error of 0.0015 g g −1, which, following an initial settling stage, becomes practically homogeneous throughout. Temperature profiles were found difficult to predict with the model. The minor spatial gradients of humidity found are governed by convection and shearing of the flow. Highlights: Creation of humidity distribution results in a test chamber with a time-varying inlet. Validation of CFD model which shall be used as a humidity predictive tool. Spatial distribution of humidity is uniform for a dehumidified jet inlet. Temporal distribution of interior humidity follows inlet variation due to good mixing.